Practical data modeling for production with Kotlin : quickly express business logic with production-ready prototypes (O'Reilly Media, 2017)
"Kotlin is a JVM platform language that fills two practical data science needs: you can use it to prototype models quickly, then effectively move those models into production. Data science values languages that provide a fast turnaround. This is why R and Python are the usual language choices for the data science domain. However, as data science continues to integrate into mainstream software development workflows, a gap has appeared. It's one thing to hack together a proof-of-concept model; it's another to move it into the 'business is evolving and models must be refactored' world of production. Kotlin closes the gap. Backed by Jetbrains and Google, Kotlin expands on the simplicity, conciseness, and elegance of Python, but carries the power, robustness, and scalability of Java and Scala. In this course, you'll get a detailed overview of Kotlin and discover why it's becoming the go-to practical language of choice for production-oriented data scientists and engineers. Learners should have Intellij IDEA and JDK, Python experience, and a little experience with basic analytics (Pandas, R, Excel, SQL, etc.)."--Resource description page